Kumon In: The Recent, Rapid Rise of Private Tutoring Centers - Edward Kim; Joshua Goodman; Martin R. West (Institute of Labor Economics (IZA), 2024)
The increasing prevalence of private tutoring has received minimal scholarly attention in the United States. We use over 25 years of geocoded data on the universe of U.S. private tutoring centers to estimate the size and growth of this industry and to identify predictors of tutoring center locations. We document four important facts. First, from 1997 to 2022, the number of private tutoring centers more than tripled, from about 3,000 to 10,000, with steady growth through 2015 before a more recent plateau. Second, the number and growth of private tutoring centers is heavily concentrated in geographic areas with high income and parental education. More than half of tutoring centers are in areas in the top quintile of income. Third, even conditional on income and parental education, private tutoring centers tend to locate in areas with many Asian American families, suggesting important differences by ethnic or cultural identity in demand for such services. Fourth, we see only marginal evidence that prevalence of private tutoring centers is related to the structure of K-12 school markets, including the prevalence of private schools and charter or magnet school options. The rapid rise in high-income families' demand for this form of private educational investment mimics phenomena observed in other spheres of education and family life, with potentially important implications for inequality in student outcomes.
Keywords: 330; education; tutoring